2012
DOI: 10.1111/j.1467-8667.2011.00752.x
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening and Rehabilitation of Reinforced Concrete Slabs with Carbon‐Fiber Reinforced Polymers Using a Refined Bond Model

Abstract: Slabs are one of the main load-bearing elements in nearly every structure. Because of additional live loads or modifications of the building structure these slabs often have to be strengthened. Using externally bonded carbon-fiber reinforced polymer (CFRP) strips to strengthen existing concrete structures has become common practice. One of the main failure modes is the loss of the composite action between the concrete and the CFRP strip making the bond force transfer very important. This bond force transfer de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Ali and Armstrong (2008) advocate the use of highstrength and light-weight composite materials such as carbon fiber reinforced composites (Finckh, Zilch 2012) proposed for a 40 story multi-use Carbon Tower designed by Peter Testa. The use of such materials will result in much lighter structures.…”
Section: High-strength and Light-weight Composite Materialsmentioning
confidence: 99%
“…Ali and Armstrong (2008) advocate the use of highstrength and light-weight composite materials such as carbon fiber reinforced composites (Finckh, Zilch 2012) proposed for a 40 story multi-use Carbon Tower designed by Peter Testa. The use of such materials will result in much lighter structures.…”
Section: High-strength and Light-weight Composite Materialsmentioning
confidence: 99%
“…The global bond stress-slip response for NSM strips subjected to a pull-out force is generally characterized by an initial, relatively stiff, linear behavior, followed by a nonlinear curve up to the maximum value of the bond stress (bond strength), after which the originated damage causes a softening branch. Moreover, in NSM strengthening systems, it has been observed the activation of a friction component for relatively large slips as an extension of the softening branch [1,14,[17][18][19]. The presence of a friction branch has been also reported in the bond behavior of other strengthening materials as fiber reinforced cementitious matrix composites (FRCM) [20,21].…”
Section: Bond Mechanisms In Nsm Frp Strengthening Systemsmentioning
confidence: 99%
“…This way, there are two main issues improving the transfer of stresses with respect to the EBR reinforcement: the higher ratio of the area of the perimeter in contact with the adhesive to the FRP area, and the transmission to the concrete material through a confined zone in the interior of the slot in the concrete cover.The global bond stress-slip response for NSM strips subjected to a pull-out force is generally characterized by an initial, relatively stiff, linear behavior, followed by a nonlinear curve up to the maximum value of the bond stress (bond strength), after which the originated damage causes a softening branch. Moreover, in NSM strengthening systems, it has been observed the activation of a friction component for relatively large slips as an extension of the softening branch [1,14,[17][18][19]. The presence of a friction branch has been also reported in the bond behavior of other strengthening materials as fiber reinforced cementitious matrix composites (FRCM) [20,21].The bond mechanisms generated in the NSM FRP technique can lead to several types of failure modes, which are mainly influenced by the bonded length, FRP surface and shape, groove configuration, materials mechanical properties and adhesive properties [22,23].…”
mentioning
confidence: 99%
“…Ngo et al (2007) studied ground floor concrete columns subjected to blast loads and found that by increasing the strength of the concrete and decreasing the spacing of the shear reinforcements the column would make them more energy absorptive and, therefore, more effective for a blast loading situation. Yusof et al (2010) investigated the behavior of steel fiber reinforced concrete panels (Finckh, Zilch 2012) with varying volumes of steel fibers and found that by increasing the volume of the steel fibers the panels became more blast resistant. Lee et al (2009) used the finite element method and computation fluid dynamics to study deep, wide flange columns often used in seismic design and found that they can be highly vulnerable under blast loads, especially in the weak axis direction.…”
Section: Introductionmentioning
confidence: 99%